2016
DOI: 10.1186/s12889-016-3684-7
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial of three very brief interventions for physical activity in primary care

Abstract: BackgroundVery brief interventions (VBIs) for physical activity are promising, but there is uncertainty about their potential effectiveness and cost. We assessed potential efficacy, feasibility, acceptability, and cost of three VBIs in primary care, in order to select the most promising intervention for evaluation in a subsequent large-scale RCT.MethodsThree hundred and ninety four adults aged 40–74 years were randomised to a Motivational (n = 83), Pedometer (n = 74), or Combined (n = 80) intervention, deliver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(38 citation statements)
references
References 25 publications
0
38
0
Order By: Relevance
“…A study investigating pedometer's accuracy according to their position worn at various walking speeds showed that at all positions, pedometers generated significant errors at slow speeds and therefore cannot be used reliably to evaluate the amount of physical activity for people walking slower than 0.6 m/s (2.16 km/h, or 1.24 mph) [15]. Regardless of that, pedometers are used in many areas such as primary care [16] increasing physical activity and stress management [17,18] decreasing cardiovascular risk factors [19] and adolescents [20]. RT6 and pedometer results were not found significantly correlated in our study.…”
Section: Discussionmentioning
confidence: 99%
“…A study investigating pedometer's accuracy according to their position worn at various walking speeds showed that at all positions, pedometers generated significant errors at slow speeds and therefore cannot be used reliably to evaluate the amount of physical activity for people walking slower than 0.6 m/s (2.16 km/h, or 1.24 mph) [15]. Regardless of that, pedometers are used in many areas such as primary care [16] increasing physical activity and stress management [17,18] decreasing cardiovascular risk factors [19] and adolescents [20]. RT6 and pedometer results were not found significantly correlated in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, because of computational difficulties for such a complex model, we limited this to a comparison between the pedometer BIs and current practice. This was chosen because we selected a pedometer intervention as the most promising VBI for trial evaluation in our wider research program [77]. Thus, the analysis established whether or not there was an economic case for a trial of a pedometer BI.…”
Section: Value Of Information Analysismentioning
confidence: 99%
“…This tool is deliverable within 5 minutes and involves a brief face‐to‐face consultation discussing the benefits of increasing PA, a goal of 10,000 steps/day, instructions in pedometer use, and a step chart to set and track daily step goals. Patients are also provided with an information booklet .…”
Section: Introductionmentioning
confidence: 99%